Benchmarking the efficiency of the Korean banking sector: a DEA approach - Sufian, Fadzlan (Emerald, 2011)
Purpose – The purpose of this paper is to critically examine the sources of inefficiency in the Korean banking sector. The present study focuses on three different approaches: intermediation approach, value-added approach, and operating approach, to differentiate how efficiency scores vary with changes in inputs and outputs.